PENGARUH LAYANAN INFORMASI TERHADAP MOTIVASI BELAJAR SANTRI KELAS X MA DAREL HIKMAH PEKANBARU TA. 2013 / 2014 - Rudi Hartono; Abu asyari; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : In the world of education there are some problems became a phenomenon and become problem that need special attention. One of it is the motivation of learning. This research was Conducted in MA Darel Hikmah Pekanbaru. The end of this research is 1). To know if there is a description of the learning motivation of students before the given information services. 2). To know the description of learning motivation of students after the given information services. 3). To to know if there is a difference between learning motivation of students before and after the given information services. The sample in this research is a student MA Darel Hikmah Pekanbaru. Before they are given information services about the learning motivation, students of class X MA Darel Hikmah Pekanbaru learning motivation is in middle category (43,59 percent). After they are given service there is increasing to middle category (61,54). the magnitude of the influence of information services to students learning motivation is measured by the correlation formula and interpretation of the determinant of the coefficient values contained on the strong category. Conclusion the results of this research are based on the calculation of thitung is greater than t_tabel (11,67 > 1,980). Thus Ho is rejected and accepted which means there are Ha a significant difference to student learning motivation MA Darel Hikmah Pekanbaru before and after the given information services.Keywords: information services, learning motivation.WISUDA OKTOBER